2010
DOI: 10.1063/1.3291680
|View full text |Cite
|
Sign up to set email alerts
|

Interplay between magnetic impurities and photoinduced carriers in surface depletion layer of anatase Ti1−xCoxO2−δ thin film probed by x-ray photoemission spectroscopy

Abstract: X-ray photoemission spectroscopy measurements with ultraviolet laser illumination have been performed for anatase Ti1−xCoxO2−δ thin films with x=0.05 and 0.10 in order to investigate the interplay between the Co spins and the photoinduced carriers in the surface region. We have found that the surface band bending is removed by the ultraviolet illumination, indicating that photoinduced carriers are injected into the surface depletion layer. After the carrier injection, the position of the chemical potential is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
10
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 23 publications
1
10
0
Order By: Relevance
“…For example, core-level XPS spectra of Ti 1-x Co x O 2 (x = 0.05 and 0.10) are shifted and narrowed by UV light illumination, indicating that the surface depletion layer and the magnitude of band bending can be controlled by the photo-induced carriers. 2 On the other hand, photo-induced effects at surfaces of strongly correlated transition-metal oxides are less explored. In such transition-metal oxides, the crystal field splits the d levels into the t 2g triplet and e g doublet, and the t 2g level or e g level is partially occupied by electrons in Ti 3+ .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…For example, core-level XPS spectra of Ti 1-x Co x O 2 (x = 0.05 and 0.10) are shifted and narrowed by UV light illumination, indicating that the surface depletion layer and the magnitude of band bending can be controlled by the photo-induced carriers. 2 On the other hand, photo-induced effects at surfaces of strongly correlated transition-metal oxides are less explored. In such transition-metal oxides, the crystal field splits the d levels into the t 2g triplet and e g doublet, and the t 2g level or e g level is partially occupied by electrons in Ti 3+ .…”
mentioning
confidence: 99%
“…We have studied surface electronic structure and light illumination effect of spineltype MgTi 2 Surface electronic structures of Ti 4+ oxides have been attracting great interest since the discovery of Honda-Fujishima effect on photocatalytic water splitting. 1 Surfaces of Ti 4+ oxides with the d 0 electronic configuration are known to show characteristic electronic structural changes under ultraviolet (UV) light illumination which can be probed by x-ray photoemission spectroscopy (XPS).…”
mentioning
confidence: 99%
“…ultraviolet illumination suggested that photoinduced carriers at a depleted layer intermediate exchange coupling between Co spins [13]. These results suggest that surface depletion possibly caused by oxidation plays a major role in reduced magnetization in (Ti,Co)O2, since the oxygen vacancies serve as an electron donor to induce the ferromagnetism [6].…”
Section: Resultsmentioning
confidence: 69%
“…In the case of (Ti,Co)O 2 , the magnetically dead layer was at least~5 nm thick [9] and could be attributed to a surface oxidation and/or a depletion layer due to the different surfaces and bulk electronic structures observed via soft and hard X-ray photoemission spectroscopy [12]. X-ray photoemission spectroscopy under ultraviolet illumination suggested that photoinduced carriers at a depleted layer intermediate exchange coupling between Co spins [13]. These results suggest that surface depletion possibly caused by oxidation plays a major role in reduced magnetization in (Ti,Co)O 2 , since the oxygen vacancies serve as an electron donor to induce the ferromagnetism [6].…”
Section: Introductionmentioning
confidence: 99%
“…There are several mechanisms of exchange coupling proposed for Co-doped TiO 2 , for example, an indirect exchange of bound magnetic polarons formed with localized carriers 4,5 and carrier mediated exchange coupling. 2,6,7 In addition, spinodal decomposition was recently proposed to explain high T C in (Ga,Mn)As, (Ga,Mn)N and other III-V ferromagnetic semiconductors. 8,9 For rutile Co-doped TiO 2 , x-ray fluorescence holography (XFH) measurement recently revealed an existence of suboxidic structure embedded in the rutile structure, which could be an alternative explanation for the high T C .…”
mentioning
confidence: 99%